2019
DOI: 10.1007/s10021-019-00350-4
|View full text |Cite
|
Sign up to set email alerts
|

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands

Abstract: Anthropogenic activities are increasing nutrient inputs to ecosystems worldwide, with consequences for global carbon and nutrient cycles. Recent meta-analyses show that aboveground primary production is often co-limited by multiple nutrients, however little is known about how root production responds to changes in nutrient availability. At twenty-nine grassland sites on four continents, we quantified shallow root biomass responses to nitrogen (N), phosphorus (P) and potassium plus micronutrient enrichment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 71 publications
3
43
1
Order By: Relevance
“…Directly following aboveground biomass collection, five soil cores were collected from the clipped area, homogenized, and a subsample of the soil (c. 60 g) was used to estimate belowground plant biomass to a depth of 10 cm (Cleland et al, ). The subsample was suspended in water, and roots were captured with fine sieves and hand‐picked.…”
Section: Methodsmentioning
confidence: 99%
“…Directly following aboveground biomass collection, five soil cores were collected from the clipped area, homogenized, and a subsample of the soil (c. 60 g) was used to estimate belowground plant biomass to a depth of 10 cm (Cleland et al, ). The subsample was suspended in water, and roots were captured with fine sieves and hand‐picked.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Graham and Mendelssohn () reported that long‐term (7 yr) additions of N reduced live root biomass of a S. lancifolia marsh, similar to our findings, but there was no effect of P. In contrast, Darby and Turner (2008 a ) found that P alone or in combination with N or Fe reduced root and rhizome biomass of salt marsh vegetation, which they attributed to decreased competition for P with the microbial community. Cleland et al () found that, in a globally distributed fertilization experiment of terrestrial grasslands, N and P applied singly reduced carbon allocated to roots and root biomass (0–10 cm), where most roots are located.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced MOM biomass in +N and +P plots relative to control and +NP plots (Table ) may be explained by the optimal allocation hypothesis (Gleeson and Tilman ). The theory predicts that when plant growth is limited by belowground resources such as nutrients, carbon allocation to roots should increase (Gleeson and Tilman ; Cleland et al ) but when the limitation is removed, in this case by fertilization, C allocation to belowground structures is reduced. This is especially true for N since reduced root foraging allows more N to be allocated aboveground where it is a component of the chlorophyll molecule and photosynthesis (Sterner and Elser ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, global patterns of root productivity are unclear. For instance, fine root biomass is high in grasslands but low in forests (Jackson et al 1997;Schenk and Jackson 2002;Cleland et al 2019). Furthermore, fine root productivity and biomass differ between life forms (Bauhus and Messier 1999;Pavon 2005).…”
Section: Introductionmentioning
confidence: 99%